Objective hyperemia and intraocular pressure changes following omidenepag isopropyl application. - Kana Tokumo; Tsuyoshi Yoneda; Yuta Nakaniida; Ryota Aoki; Shunsuke Nakakura; Taro Baba; Naoki Okada; Ayaka Edo; Hiromitsu Onoe; Hideaki Okumichi; Kazuyuki Hirooka; Diane Sonassa; et al. (PLoS ONE)
Conjunctival hyperemia was the most common adverse drug reaction to the ophthalmic solution omidenepag isopropyl in a post-marketing observational study. Here, we prospectively examined changes in hyperemia from before to 3 months after the initiation of the omidenepag isopropyl, a selective E-prostanoid receptor-2 receptor agonist, using hyperemia analysis software. Subjects were glaucoma patients who started omidenepag isopropyl use at Hiroshima University Hospital and Saneikai Tsukazaki Hospital. Hyperemia was compared by calculating the percentage coverage of vessels on the apex side using hyperemia analysis software based on anterior segment images. A total of 45 patients were enrolled, with 19 eyes in the new administration treatment group and 26 eyes in the group switched from F-prostanoid receptor agonists. Following switching from F-prostanoid receptor agonists to omidenepag isopropyl, there was no significant change in the hyperemia area from 7.4 (5.7-8.8) % to 7.4 (5.3-8.3)% (P = 0.53, Wilcoxon signed-rank test). In the new administration group, the hyperemia area increased significantly from7.0 (5.2-8.6) % to 8.2 (6.4-9.1) % (P = 0.02, Wilcoxon signed-rank test). There was no significant change in intraocular pressure (IOP) from 15.0 (12.0-17.0) mmHg to 14.0 (12.0-15.0) mmHg in the switching group (P = 0.37, Wilcoxon signed-rank test), whereas there was a significant IOP reduction from 15.0 (13.5-18.5) mmHg to 15.0 (11.0-16.5) mmHg (P = 0.03, Wilcoxon signed-rank test) in the new administration group. One eye in the new administration group that developed macular edema during the observation period resolved spontaneously upon discontinuing omidenepag isopropyl. Both hyperemia and IOP reduction with omidenepag isopropyl ophthalmic solution were comparable to those achieved with F-prostanoid receptor agonists.